Mercury ion responsive linear polymer and polymer smart gel and preparation method thereof

The polymer material formed by copolymerization of N-isopropylacrylamide and allyl barbituric acid monomers uses barbituric acid structural units to form a 1:1 coordination compound with mercury ions, solving the problem of low selective recognition ability of existing materials for mercury ions and trivalent ions, and achieving efficient, economical and specific recognition of mercury ions.

CN119350544BActive Publication Date: 2025-03-18SICHUAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411886985.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-18
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The existing mercury ion recognition polymer materials have low selective recognition ability of mercury ions and trivalent ions, resulting in interference of trivalent ions on mercury ions detection.

Method used

The mercury ion-responsive linear polymer and polymer smart gel formed by copolymerization of N-isopropylacrylamide and allyl barbituric acid monomers form a 1:1 coordination compound with mercury ions through barbituric acid structural units, achieving specific identification of mercury ions.

Benefits of technology

It improves the specific recognition ability of mercury ions, reduces the difficulty and cost of preparation of mercury ion detection materials, and realizes the sensitivity, convenience and low-cost detection of mercury ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350544B_ABST
    Figure CN119350544B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of polymer compounds and mercury ion detection, and provides mercury ion responsive linear polymers and polymer smart gels and preparation methods thereof. The mercury ion responsive linear polymer of the present invention is poly(N-isopropylacrylamide-co-allylbarbituric acid), which is formed by one-step copolymerization of N-isopropylacrylamide monomers and allylbarbituric acid monomers. The mercury ion responsive linear polymer of the present invention has excellent specific recognition ability for mercury ions, which can solve the problem that the selective recognition ability of existing mercury ion recognition polymer materials for mercury ions and trivalent ions is not high. The mercury ion responsive polymer smart gel of the present invention is polymerized by N-isopropylacrylamide monomers, allylbarbituric acid monomers and cross-linking agents. The operation of detecting mercury ions or adsorbing and removing mercury ions in water based on the smart gel is simple, and has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer compounds and mercury ion detection, and relates to mercury ion responsive linear polymers and polymer smart gels and preparation methods thereof. Background Art

[0002] Mercury is a highly toxic heavy metal element that is harmful to the human body and has a variety of uses in industry. Industrial or natural activities such as mining, fossil fuels, volcanic emissions and agriculture will gradually release mercury into surface water and groundwater, posing a huge threat to environmental water resources. Currently, mercury is listed as a Class I water pollutant. Since the 1990s, the total amount of mercury entering the ocean is estimated to be 200,000 tons, and mercury pollution has attracted widespread attention worldwide. Mercury in nature is mainly present in the form of elemental mercury (Hg), inorganic mercury (Hg + Salt, Hg 2+ Mercury exists in the form of organic mercury (salts and their complexes) and organic mercury (alkyl mercury and phenyl mercury), and can undergo a variety of biological and chemical transformations. Even if a small amount of mercury is inhaled or accidentally ingested, it can cause serious damage to the reproductive system, gastrointestinal tract, cardiovascular system and nervous system. In addition, various forms of mercury are difficult to degrade. Once absorbed by aquatic organisms, they will accumulate in the body of aquatic organisms for a long time, and be transmitted through the food chain, and eventually enriched in the human body. When the mercury content in the body reaches a certain concentration, the normal physiological functions of the human body will be disturbed, and it will lead to a variety of diseases, such as methylmercury poisoning, Minamata disease, Alzheimer's disease, etc. Mercury ion (Hg 2+ ) is the most stable and common inorganic mercury. The health reference level of mercury ions in drinking water in my country is 4.98×10 -9 mol / L. Therefore, the development of a highly selective, simple and sensitive mercury ion detection method is of great significance for the monitoring of drinking water and environmental water quality.

[0003] High-precision detection of mercury ions can be achieved through traditional methods such as inductively coupled plasma mass spectrometry, atomic absorption spectroscopy and atomic fluorescence spectroscopy. However, these methods rely on expensive and sophisticated instruments, complex sample preparation processes and complex instrument operation processes, which are difficult to meet the low-cost, portable and simple detection needs of mercury ions. In recent years, some emerging detection technologies have emerged, such as colorimetry, fluorescence detection analysis and electrochemical analysis. The concentration signal of mercury ions is converted into color, light or electrical signals through specific detection materials, thereby realizing the detection of mercury ion concentration, which reduces the detection cost of mercury ions to a certain extent. However, the color signals generated by these detection methods have strong individual differences in reading, and the generated light, electricity and other signals still need to rely on some large laboratory instruments, such as fluorescence spectrophotometers, electrochemical workstations, etc. for detection, and it is still difficult to achieve accurate or low-cost detection of mercury ions. In addition, although some materials have demonstrated excellent mercury ion-specific recognition performance, the synthesis process of these raw materials is complex and has strict requirements on preparation conditions. In addition, some organic synthetic probes, polymer materials and metal-organic framework materials have certain toxicity, and their application and recycling will increase the environmental burden.

[0004] CN116239720A discloses a thermosensitive linear polymer material with dual base surface recognition of mercuric ions and a preparation method thereof, wherein the thermosensitive linear polymer material is synthesized by copolymerization of N-isopropylacrylamide and a barbituric acid derivative. Although this method reduces the difficulty of preparing existing mercury ion detection materials, the thermosensitive linear polymer material is sensitive to mercury ions and trivalent ions (such as Al 3+ Cr 3+ , Fe 3+ The selective recognition ability of mercury ions is not high. When identifying mercury ions, they will also identify trivalent ions, so the interference of trivalent ions on mercury ion detection cannot be avoided. Therefore, it is necessary to develop mercury ion recognition materials with simple synthesis methods and better specific recognition performance for mercury ions. Summary of the invention

[0005] In view of the problem that existing mercury ion recognition polymer materials have low selective recognition ability for mercury ions and trivalent ions, the present invention provides mercury ion responsive linear polymers and polymer smart gels and preparation methods thereof, so as to improve the specific recognition ability for mercury ions while reducing the difficulty of preparing existing mercury ion detection materials, thereby providing new materials for sensitive, convenient and low-cost detection of mercury ions.

[0006] In order to achieve the above-mentioned invention object, the technical solution provided by the present invention is as follows:

[0007] A mercury ion responsive linear polymer, the structural formula of the linear polymer is shown in formula (I):

[0008] (I)

[0009] In formula (I), b / (a+b)=0.05~0.11.

[0010] Furthermore, in formula (I) of the technical solution of the mercury ion responsive linear polymer, b / (a+b)=0.07~0.11.

[0011] The present invention also provides a method for preparing the mercury ion responsive linear polymer, comprising the following steps:

[0012] (1) N-isopropylacrylamide monomer, allyl barbituric acid monomer and initiator are dissolved in a solvent to obtain a mixed solution, nitrogen is passed through the mixed solution to remove oxygen in the mixed solution, and then the mixture is heated in a sealed container at 65-80°C. ℃ reaction 12~36 hours;

[0013] In this step, the molar ratio of the N-isopropylacrylamide monomer to the initiator in the mixed solution is controlled to be (100-200): (0.05-0.5), and the molar amount of the allylbarbituric acid monomer accounts for 5%-11% of the sum of the molar amounts of the allylbarbituric acid monomer and the N-isopropylacrylamide monomer;

[0014] (2) Separating and purifying the mercury ion-responsive linear polymer from the reaction solution obtained in step (1) by a precipitation method.

[0015] In the technical solution of the above-mentioned method for preparing mercury ion responsive linear polymer, the concentration of N-isopropylacrylamide monomer in the mixed solution of step (1) is preferably 0.1-0.4 mol / L.

[0016] In the technical scheme of the preparation method of the mercury ion responsive linear polymer, the initiator in step (1) is a thermal initiator. For example, feasible initiators include azobisisobutyronitrile, azobisisoheptanenitrile or dimethyl azobisisobutyrate.

[0017] In the technical scheme of the preparation method of the mercury ion responsive linear polymer, the solvent in step (1) is tetrahydrofuran, N, N-dimethylformamide or 1, 4-dioxane.

[0018] In the technical solution of the above-mentioned method for preparing mercury ion responsive linear polymer, the operation of separating and purifying the mercury ion responsive linear polymer from the reaction solution obtained in step (1) by precipitation method is as follows:

[0019] The reaction solution obtained in step (1) is concentrated until insoluble matter is just produced, and solvent A is added to the concentrated reaction solution to dissolve the insoluble matter just enough, and the resulting solution is added dropwise to a large amount of solvent B in a stirring state for precipitation, filtered, and the resulting solid phase is dried, and the above-mentioned dissolution with solvent A, precipitation with solvent B, filtering and drying are repeated 2 to 3 times to obtain the product. The solvent A is tetrahydrofuran, N, N-dimethylformamide or 1, 4-dioxane, and the solvent B is anhydrous ether or n-hexane.

[0020] The present invention also provides a mercury ion responsive polymer smart gel, the polymer structure of the polymer smart gel is shown in formula (II):

[0021] (II)

[0022] In formula (II), b / (a+b)= 0.05~0.13, c / a=0.01~0.07.

[0023] The present invention also provides a method for preparing the mercury ion responsive polymer smart gel, comprising the following steps:

[0024] Dissolving N-isopropylacrylamide monomer, allylbarbituric acid monomer, initiator and cross-linking agent N,N'-methylenebisacrylamide in water to obtain a mixed solution, passing nitrogen gas into the mixed solution to remove oxygen in the mixed solution, then adding a catalyst to obtain a gel precursor solution, reacting the gel precursor solution at 10-25° C. until it is converted into a gel state, and washing to remove unreacted raw materials to obtain;

[0025] In the gel precursor solution, the molar ratio of N-isopropylacrylamide monomer to initiator is (100~200):(0.05~0.5), the molar ratio of N-isopropylacrylamide monomer to cross-linking agent is 100:(1~7), the molar amount of allylbarbituric acid monomer accounts for 5%~13% of the sum of the molar amounts of allylbarbituric acid monomer and N-isopropylacrylamide monomer, and the concentration of N-isopropylacrylamide monomer is 0.5~1.5 mol / L.

[0026] In the technical solution of the preparation method of the mercury ion responsive polymer smart gel, the catalyst is tetramethylethylenediamine.

[0027] In the technical solution of the method for preparing the mercury ion responsive polymer smart gel, the initiator is an initiator that can initiate a polymerization reaction at room temperature. For example, feasible initiators include ammonium persulfate or potassium persulfate.

[0028] The principle of the mercury ion responsive linear polymer and mercury ion responsive polymer smart gel provided by the present invention to achieve specific recognition of mercury ions is as follows:

[0029] The mercury ion responsive linear polymer provided by the present invention is formed by one-step copolymerization of N-isopropylacrylamide monomer and allyl barbituric acid monomer. The barbituric acid structural unit on the molecular chain of the linear polymer has a special hydrogen bond donor and hydrogen bond acceptor, and can form a 1:1 coordination compound with mercury ions under the induction of mercury ions. On the one hand, the hydrogen bond between the barbituric acid unit and water is broken after binding with mercury ions, thereby reducing the number of hydrogen bonds between the linear polymer and water. On the other hand, the linear polymer is [-C1B-Hg 2+ -C1B-Hg 2+ -C1B-] structure is pulled tighter, which can accelerate the transformation of the linear polymer molecular chain from the hydrogen bonding mode of amide and water to the hydrogen bonding mode of amide and amide in the linear polymer molecular chain itself, showing obvious isothermal phase transition behavior, making the linear polymer have obvious mercury ion responsiveness.

[0030] The three-dimensional polymer network of the mercury ion responsive polymer smart gel provided by the present invention is formed by copolymerization of N-isopropylacrylamide monomer, allyl barbituric acid monomer and a cross-linking agent. The barbituric acid structural unit in the three-dimensional polymer network of the polymer smart gel has special hydrogen bond donors and hydrogen bond acceptors, which can increase the water content of the swelling equilibrium of the polymer smart gel in an aqueous solution. When the solution contains mercury ions, the barbituric acid structure on the gel skeleton can form a 1:1 coordination compound with the mercury ions under the induction of the mercury ions. On the one hand, the hydrogen bond between the barbituric acid unit and water is broken after combining with the mercury ions, thereby reducing the number of hydrogen bonds between the three-dimensional polymer network and water. On the other hand, the three-dimensional polymer network is [-C1B-Hg 2+ -C1B-Hg 2+ -C1B-] structure is pulled tighter, which can squeeze out the water molecules in the three-dimensional polymer network, causing the gel volume to shrink, thereby achieving specific recognition of mercury ions.

[0031] Compared with the prior art, the technical solution provided by the present invention produces the following beneficial technical effects:

[0032] 1. The present invention provides a mercury ion responsive linear polymer, which is formed by one-step copolymerization of N-isopropylacrylamide monomer and allyl barbituric acid monomer. The present invention has been experimentally confirmed that the mercury ion responsive linear polymer has good temperature sensitivity, and the barbituric acid structure on the molecular chain of the mercury ion responsive linear polymer can form a 1:1 coordination compound with mercury ions under the induction of mercury ions, causing the molecular chain of the linear polymer to shrink, resulting in a decrease in the solubility of the linear polymer in the solution, and showing obvious isothermal phase transition behavior. Since allyl barbituric acid is a hydrophilic monomer, the mercury ion responsive linear polymer formed by copolymerization with N-isopropylacrylamide has a higher phase transition temperature than the linear polymer formed by polymerization of N-isopropylacrylamide alone, so that the mercury ion detection process is not easily disturbed by the ambient temperature. In addition, the barbituric acid structure is connected to the polymer chain only through a short alkane chain, which is conducive to the linear polymer to bind mercury ions more quickly and with low steric hindrance, without interference from other functional groups, and exhibits excellent anti-interference properties against monovalent, divalent and trivalent metal ions, effectively improving the specific recognition ability of existing mercury ion detection materials for mercury ions.

[0033] 2. The present invention also provides a method for preparing the above-mentioned mercury ion responsive linear polymer. Since the functional monomer allyl barbituric acid used in the method has a simple structure and contains only one carbon-carbon double bond, there is no need to use other complicated methods to regulate the addition position during the copolymerization reaction. The synthesis method of the mercury ion responsive linear polymer is very simple, which is beneficial to reducing the difficulty and cost of preparing mercury ion detection materials and realizing cost-effective detection of mercury ions.

[0034] 3. The present invention also provides a mercury ion responsive polymer smart gel, which is polymerized by N-isopropylacrylamide monomer, allyl barbituric acid monomer and cross-linking agent. The mercury ion responsive polymer smart gel has good mercury ion responsiveness. In the presence of mercury ions, the barbituric acid structure in the three-dimensional network skeleton of the smart gel material can form a 1:1 coordination compound with mercury ions under the induction of mercury ions, pull the distance between the three-dimensional network skeleton of the gel, thereby squeezing out the water molecules in the pores of the three-dimensional network, and then converting the mercury ion concentration signal into a gel volume contraction signal that is easy to measure macroscopically. On this basis, the relationship between the gel volume contraction degree and the mercury ion concentration of the solution is established, and the mercury ion concentration of unknown concentration can be quantitatively measured. The gel has good adsorption capacity for mercury ions, and the mercury ions bound to the gel can be easily eluted in the NaI solution. The eluted smart gel can be reused and has strong durability. The operation of detecting mercury ions or adsorbing and removing mercury ions in water based on the smart gel is simple and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1This is the synthesis route of the mercury ion responsive monomer allyl barbituric acid (C1B) in Example 1.

[0036] Figure 2 This is the H NMR spectrum of C1B prepared in Example 1.

[0037] Figure 3 Figure a) is the UV absorption spectrum of C1B in solutions with different mercury ion concentrations. Figure 3 Figure b) is the UV absorption spectrum of C1B in metal ion solutions of different ion types. Figure 3 c) is the curve of the change of ultraviolet absorption intensity of C1B with mercury ion concentration. Figure 3 The graph d) shows the value of [1(A0-A)] of C1B and 1 / [Hg 2+ ] is the fitting relationship curve between .

[0038] Figure 4 This is the synthesis route of the mercury ion responsive linear polymer in Example 3.

[0039] Figure 5 Figure a) is the P(NIPAM- co -C1B) and the UV spectra of PNIPAM prepared in Comparative Example 1, Figure 5 Figure b) is the P(NIPAM- co -C1B) and infrared spectra of PNIPAM prepared in Comparative Example 1.

[0040] Figure 6 The P(NIPAM- co -BBA) H NMR spectrum.

[0041] Figure 7 Figure a) is the preparation of P(NIPAM- co -C1B) H NMR spectrum, Figure 7 The b) graph is Figure 7 a) An enlarged view of the dotted box in Figure .

[0042] Figure 8 Figure a) is a curve showing the change of the transmittance of PNIPAM prepared in comparative example 1 in deionized water and mercury ion solution as a function of temperature. Figure 8 FIG. b) is a curve showing the change of transmittance of PNC-5 prepared in Example 4 in deionized water and mercury ion solution with temperature. Figure 8 Figure c) is a curve showing the change of transmittance of PNC-7 prepared in Example 4 in deionized water and mercury ion solution as a function of temperature. Figure 8Figure d) is a curve showing the change of transmittance of PNC-9 prepared in Example 3 in deionized water and mercury ion solution with temperature. Figure 8 Figure e) is a curve showing the change in transmittance of PNC-11 prepared in Example 4 in deionized water and mercury ion solution as a function of temperature.

[0043] Fig. 9 Figure a) is a curve showing the change of transmittance of PBA-5 prepared in comparative example 2 in deionized water and mercury ion solution as a function of temperature. Fig. 9 Figure b) is a curve showing the change in transmittance of PBA-7, PBA-9 and PBA-11 prepared in comparative example 2 in deionized water and mercury ion solution as a function of temperature.

[0044] Fig.10 Figure a) shows the LCST of PNIPAM prepared in Example 1 and PNC-5, PNC-7, PNC-9, and PNC-11 prepared in Examples 3 and 4 in deionized water and mercury ion solution. Fig.10 Figure b) shows the ΔLCST of PNIPAM prepared in Comparative Example 1 and PNC-5, PNC-7, PNC-9, and PNC-11 prepared in Examples 3 and 4. Fig.10 Figure c) shows the LCST of PNIPAM prepared in Example 1 and PBA-5, PBA-7, PBA-9, and PBA-11 prepared in Example 2 in deionized water and mercury ion solution. Fig.10 d) shows the ΔLCST of PNIPAM prepared in Comparative Example 1 and PBA-5 prepared in Comparative Example 2.

[0045] Fig.11 It is a comparison chart of ΔLCST of PNC-9 prepared in Example 3 and PBA-5 prepared in Comparative Example 2 in different ionic solutions.

[0046] Fig.12 Figure a) is the UV spectrum of C1B under different pH conditions. Fig.12 Figure b) shows the p value of C1B under different pH conditions. K aTest results, Fig.12 Figure c) is the UV spectrum of PNC-9 prepared in Example 3 under different pH conditions, Fig.12 d) is the p of PNC-9 prepared in Example 3 under different pH conditions K aTest results.

[0047] Fig.13 Figure a) shows the LCST of PNC-9 prepared in Example 3 in deionized water and mercury ion solutions under different pH conditions. Fig.13 Figure b) shows the ΔLCST of PNC-9 prepared in Example 3 under different pH conditions.

[0048] Fig.14 This is the synthesis route of the mercury ion responsive polymer smart gel in Example 9.

[0049] Fig.15 It is the infrared spectra of C1B, PNC-H prepared in Examples 9 and 10, and PNIPAM-H prepared in Comparative Example 3.

[0050] Fig.16 Figure a) is a curve showing the change in diameter of the PNC-H-5 disc gel prepared in Example 10 in deionized water and mercury ion solution as a function of temperature, Fig.16 FIG. b) is a curve showing the change in diameter of the PNC-H-7 disc gel prepared in Example 10 in deionized water and mercury ion solution as a function of temperature. Fig.16 Figure c) is a curve showing the change in diameter of the PNC-H-9 disc gel prepared in Example 9 in deionized water and mercury ion solution as a function of temperature, Fig.16 d) is a curve showing the change in diameter of the PNC-H-11 disc gel prepared in Example 10 in deionized water and mercury ion solution as a function of temperature, Fig.16 Figure e) is a curve showing the change in diameter of the PNC-H-13 disc gel prepared in Example 10 in deionized water and mercury ion solution as a function of temperature.

[0051] Fig.17 1 is a fitting relationship curve between the diameter contraction ratio of the PNC-H-9 disc gel prepared in Example 9 in mercury ion solutions of different concentrations and the mercury ion concentration.

[0052] Fig.18 Figure a) shows the diameter shrinkage degree of the PBA-H-5 disc gel prepared in Example 4 in solutions with different metal ions. Fig.18 FIG. b) shows the diameter shrinkage degree of the PNC-H-9 disc gel prepared in Example 9 in solutions of different metal ions.

[0053] Fig.19 Figure a) shows the change in the diameter of the PNC-H-9 disc gel prepared in Example 9 with the number of cycles used, Fig.19 FIG. b) shows the change in the diameter shrinkage ratio of the PNC-H-9 disc gel prepared in Example 9 with the number of cycles. DETAILED DESCRIPTION

[0054] The mercury ion responsive linear polymer and polymer smart gel material provided by the present invention and the preparation method thereof are further described by way of examples below. In the following examples and comparative examples, N-isopropylacrylamide (NIPAM) was recrystallized with n-hexane / acetone before use, and other solvents or reactants were purchased from Sigma. The infrared spectrophotometer model used was IS50 (Thermo Fisher Scientific), the nuclear magnetic resonance model was Bruker-400 (Bruker), and the ultraviolet spectrophotometer model was Shimadzu UV-1800.

[0055] Example 1

[0056] In this embodiment, according to Figure 1 The route shown is to synthesize the mercury ion responsive monomer allyl barbituric acid (C1B), whose structural formula is as follows:

[0057]

[0058] (1) Add the catalyst sodium ethoxide (C2H5ONa) to anhydrous ethanol (Ethanol) and stir at 80°C for 10 min to fully dissolve the sodium ethoxide. Then add diethyl allylmalonate and reflux in an oil bath at 80°C for 20 min. Then, add urea to the resulting mixture while stirring and continue to reflux in an oil bath at 80°C for 4 h.

[0059] In this step, the molar ratio of sodium ethoxide to diethyl allyl malonate is controlled to be 1:1, the molar ratio of diethyl allyl malonate to urea is controlled to be 1:1.2, and the concentration of diethyl allyl malonate in the solution is 0.7 mol / L.

[0060] (2) The reaction solution obtained after the reaction in step (1) is filtered, and the obtained solid phase is dissolved with deionized water. The pH value of the obtained solution is adjusted to 2-3, and then insoluble matter is generated. The insoluble matter is filtered, and the obtained solid phase is recrystallized with anhydrous ethanol. The obtained crystals are dried to obtain C1B.

[0061] The UV spectrum of C1B prepared in this example is as follows Figure 5 As shown in the C1B curve in Figure a), C1B has a characteristic absorption peak at 267 nm, which is due to the absorption band generated by the carbonyl n→π* transition of the amide group in C1B. The infrared spectrum of C1B prepared in this example is shown in Figure 5 As shown in the C1B curve in Figure b), 3244 cm -1 The strong peak at 1640 cm -1 The weak peak at 3095 cm is caused by the stretching vibration of the carbon-carbon double bond. -1The peak at 1710 cm is caused by the stretching vibration of =CH -1 and 1735 cm -1 The peak at is caused by two different chemical environments of C=O in the structure. The above results show that C1B was successfully synthesized in this example.

[0062] The H NMR spectrum of C1B in this example is as follows Figure 2 As shown, the peak at the chemical shift of 11.23 ppm belongs to the hydrogen of the two symmetrical imino groups of barbituric acid, and the peaks at the chemical shifts of 5.63-5.573 ppm and 5.02-5.06 ppm are the peaks on the double bond -CH=CH2. These two peaks are affected by the different environmental hydrogens of the left and right adjacent positions, and are split into sextet and triplet, respectively. The peak at the chemical shift of 3.7 ppm belongs to the hydrogen in the methine group, and the characteristic peak at the chemical shift of 2.6 ppm is the peak of the methylene group. The nuclear magnetic hydrogen spectrum shows that the structure of the target product is correct, and there is basically no impurity peak, and the target product has high purity, which further illustrates that C1B is successfully synthesized in this embodiment.

[0063] Example 2

[0064] In this example, the response performance and mercury ion specific recognition performance of C1B prepared in Example 1 to different mercury ion concentrations were measured. The concentration of C1B was controlled to be 0.06 mmol / L during the measurement. 2+ ) concentration is 0~0.1mmol / L, other metal ions (metal ions include: K + , Rb + 、Na + , Li + 、Ag + , Cu 2+ , Pb 2+ , Ba 2+ Mg 2+ 、Zn 2+ , Sr 2+ 、Co 2+ , Ca 2+ , Hg 2+ 、Al 3+ , Fe 3+ Cr 3+ ) concentration was 0.1 mmol / L.

[0065] C1B was added to solutions with different mercury ion concentrations and solutions of various metal ions, and the UV spectra of C1B in solutions with different mercury ion concentrations and different metal ions were tested. The results are as follows: Figure 3 As shown. Figure 3As shown in Figure a), C1B has good mercury ion responsiveness. As the mercury ion concentration gradually increases, the ultraviolet absorption intensity of C1B gradually decreases, and the optimal absorption peak red-shifts from 266 nm to 276 nm. This may be due to the combination of mercury ions and C1B, which causes the monomers to aggregate and form a larger conjugated system, thereby causing the red shift of the system's ultraviolet absorption. Figure 3 As shown in Figure c), when [Hg 2+ ](Hg 2+ When [C1B] (C1B concentration) ≤ [C1B] (C1B concentration), the absorbance of C1B at a wavelength of 266 nm shows a linear relationship with the mercury ion concentration, and the equation of the fitting curve is A = 10.703 [Hg 2+ ]+1.0061, R 2 =0.9902. When [Hg 2+ ]>[C1B], the UV absorption intensity basically no longer decreases, which indicates that the binding mode between C1B and mercury ions is 1:1. According to the formula LOD=3σ / S, the detection limit of C1B for mercury ions is calculated to be 5.76×10 -7 mol / L, in the formula LOD=3σ / S, σ is the standard deviation of the absorbance of the blank sample (C1B aqueous solution with a concentration of 0.06 mmol / L) at a wavelength of 266 nm, the number of measurements is 12 times, and S is the slope of the above fitting curve. When the mercury ion concentration is 0~0.06mmol / L, the value of [1(A0-A)] and 1 / [Hg 2+ ] also have a good linear relationship, where A0 is the absorbance of C1B solution (C1B concentration is 0.06 mmol / L) at 266 nm in a mercury-free environment, and A is the absorbance of C1B solutions with different concentrations of mercury ions (C1B concentration is 0.06 mmol / L) at 266 nm. The value of [1(A0-A)] of C1B is related to 1 / [Hg 2+ The fitting relationship curve between Figure 3 As shown in Figure d), y in the fitting relationship represents [1(A0-A)], and x represents 1 / [Hg 2+ ], from which the complexation parameter of C1B and mercury ion can be calculated to be 1.285×10 4 M -1 .

[0066] like Figure 3 As shown in Figure b), by comparing the changes in the UV absorption of C1B in different ion solutions, it is found that only when mercury ions are present in the solution, the UV absorbance of the solution will decrease significantly, while the UV absorption of C1B in other ion solutions remains basically unchanged. This shows that C1B has good selectivity for mercury ions and can be used for the selective identification of mercury ions.

[0067] Example 3

[0068] In this embodiment, according to Figure 4 The route shown is to synthesize a mercury ion responsive linear polymer, poly(N-isopropylacrylamide-co-allylbarbituric acid) (P(NIPAM- co -C1B)), whose structural formula is as follows:

[0069]

[0070] Among them, b / (a+b)=0.09.

[0071] (1) Add monomers NIPAM and C1B and initiator azobisisobutyronitrile (AIBN) into tetrahydrofuran (THF) solvent and stir until all components are fully dissolved to obtain a mixed solution. Pass nitrogen gas through the mixed solution for 30 min under stirring to remove oxygen from the mixed solution. Then quickly transfer the mixture to a sealed container and react in an oil bath at 70°C for 24 h.

[0072] In this step, the molar ratio of NIPAM to AIBN was controlled to be 100:0.5, the molar amount of C1B accounted for 9% of the sum of the molar amounts of C1B and NIPAM, and the concentration of NIPAM in the mixed solution was 0.4 mol / L.

[0073] (2) The reaction solution obtained in step (1) is concentrated by a rotary evaporator until insoluble matter is just produced, tetrahydrofuran is added to the concentrated reaction solution to completely dissolve the insoluble matter, and then the resulting solution is added dropwise to a large amount of anhydrous ether in a stirring state for precipitation, and then filtered. The resulting solid phase is vacuum dried, and the above-mentioned steps of adding tetrahydrofuran to dissolve, precipitating with anhydrous ether, filtering and vacuum drying are repeated three times for the resulting crude product to obtain P(NIPAM- co -C1B), denoted as PNC-9.

[0074] Comparative Example 1

[0075] The operation of this comparative example is basically the same as that of Example 1, except that the C1B monomer is not added in step (1), and the product prepared is poly(N-isopropylacrylamide), denoted as PNIPAM.

[0076] Comparative Example 2

[0077] In this comparative example, a linear polymer, poly(N-isopropylacrylamide-co-barbituric acid derivative) (P(NIPAM- co-BBA)), specifically including PBA-5, PBA-7, PBA-9 and PBA-11 in Examples 2 to 3 of CN 116239720 A.

[0078] Comparative Example 2 P(NIPAM- co- BBA) Figure 6 As shown by Figure 6 It can be seen that in P(NIPAM- co- In the P(NIPAM- co- The characteristic peak of the unsaturated double bond of the benzene ring end group (CH2=CH, 5.5~7.0 ppm) is still retained in BBA, indicating that when BBA monomer is copolymerized to form a polymer, the two double bonds in BBA will undergo copolymerization to form a complex polymer structure. The specific structural formula is shown in the following formula, where the structure on the right is a polymer chain formed by cross-linking with the double bonds adjacent to the benzene ring, which has a very large steric hindrance. This structure may cause P(NIPAM- co- The polymer chain contraction of BBA is hindered after binding to mercury ions, which leads to the loss of phase transition behavior of PBA-9 and PBA-11 after recognizing mercury ions.

[0079]

[0080] Among them, (y+z) / (x+y+z)=0.05~0.11.

[0081] Example 4

[0082] In this embodiment, the synthesis of P(NIPAM- co -C1B), the specific preparation method is basically the same as that of Example 3, except that in step (1), the molar amount of C1B monomer accounts for 5%, 7%, and 11% of the sum of the molar amounts of C1B monomer and NIPAM monomer, respectively. co -C1B) are denoted as PNC-5, PNC-7, and PNC-11, respectively.

[0083] In Examples 3 and 4, the raw material C1B and the prepared P(NIPAM- co -C1B) and the ultraviolet spectra and infrared spectra of PNIPAM prepared in Comparative Example 1 are as follows Figure 5 As shown in Figures a) and b). Figure 5As shown in Figure a), PNC-5, PNC-7, PNC-9 and PNC-11 also have an absorption peak belonging to C1B at a wavelength of 267 nm, and the intensity of the absorption peak increases with the increase of C1B content. Figure 5 As shown in Figure b), the C1B monomer has a peak at 1710 cm -1 and 1735 cm -1 There are two groups of C=O stretching vibration peaks at 1650cm-1, which is caused by the carbon groups with two chemical environments on the C1B monomer; and the amide characteristic absorption peak of PNIPAM appears at 1650cm-1. -1 At 1380cm -1 and 1360cm -1 The characteristic absorption peak of the isopropyl group of NIPAM appeared at 100°; the characteristic absorption peaks of C1B and PNIPAM also appeared in the infrared spectra of PNC-5, PNC-7, PNC-9 and PNC-11, and the intensity of the characteristic peak of C1B became stronger with the increase of C1B content. This shows that a series of P(NIPAM) with different C1B contents were successfully prepared in Examples 3 and 4. -co- C1B).

[0084] P(NIPAM- co -C1B) H NMR spectrum Figure 7 As shown in the figure, we can see the obvious characteristic peaks of NIPAM (1.05 ppm, -CH(CH3)2) and C1B (10.9~11.6 ppm, NH4+), which further indicates that P(NIPAM- co Since the C1B monomer structure contains only one double bond, the formed polymer structure is clear, and compared with the BBA monomer used in CN 116239720 A, there is no problem of multi-polymerization.

[0085] Example 5

[0086] In this example, the PNIPAM, PBA-5, PBA-7, PBA-9, PBA-11, PNC-5, PNC-7, PNC-9, and PNC-11 prepared in Comparative Examples 1 and 2 and Examples 3 and 4 were tested in deionized water and mercury ions (Hg 2+ ) solution, as well as the lower critical solution temperature (LCST) and its migration value (ΔLCST).

[0087] Accurately weigh PNIPAM, PNC-5, PNC-7, PNC-9, PNC-11, PBA-5, PBA-7, PBA-9 and PBA-11, and dissolve them in deionized water and 1 mmol / L mercury ion solution, respectively. The concentration of each polymer in deionized water and mercury ion solution is controlled to be 0.1 wt%. Select multiple different temperature points (20~60℃ or 15~51℃) to test the transmittance of each solution at a wavelength of 500 nm. The test results are as follows: Figure 8 , Fig. 9 As shown, Fig.10 are the LCST and ΔLCST of each polymer in deionized water and mercury ion solution.

[0088] from Fig.10 As shown in Figure a), as the content of C1B increases, P(NIPAM -co- The LCST of C1B) in deionized water gradually shifts to a higher temperature. The main reason is that the C1B monomer is hydrophilic, and the introduction of P(NIPAM) into the PNIPAM chain increases the -co- C1B) and water molecules, thereby making P(NIPAM -co- The LCST of P(NIPAM) shifts to a higher temperature. -co- The LCST of C1B in 1 mmol / L mercury ion solution showed a gradually decreasing trend. As the C1B content continued to increase, when there was sufficient mercury ion, mercury ion immediately reacted with P(NIPAM -co- C1B) on the molecular chain, on the one hand, this [-C1B-Hg 2+ -C1B-Hg 2+ -C1B-] structure reduces the P(NIPAM -co- The number of hydrogen bonds between C1B and water on C1B) is calculated. Mercury ions act as crosslinkers to bind P(NIPAM) in the solution. -co- On the other hand, due to this interaction, the amide groups in PNIPAM are pulled closer, and then as the temperature rises, the hydrogen bond conversion from amide-water to amide-amide mode in the PNIPAM chain is promoted, and the isopropyl group can be more easily exposed to the outside of the PNIPAM polymer chain. Under the combined effect of the above factors, P(NIPAM -co- Therefore, the LCST of PNC-5, PNC-7, PNC-9, and PNC-11 in mercury ion solution showed a gradual downward trend.

[0089] like Fig.10As shown in Figure c, in deionized water, since BBA molecules are hydrophobic, when they are introduced into the PNIPAM chain through copolymerization, as the BBA monomer content gradually increases, from PBA-5 to PBA-11, the LCST migrates to low temperature, and the solubility of PBA-9 and PBA-11 is very poor. In the mercuric ion solution, mercury ions can combine with the BBA on the molecular chain of PBA-5, which can promote the P(NIPAM -co- However, as the content of BBA monomer increases, the content of hydrophobic benzene ring increases, and the double bond connecting the benzene ring and the barbituric acid mother ring limits the phase transition of P(NIPAM) to a certain extent. -co- On the other hand, the PNIPAM chain also contains a barbituric acid mother ring, which will also increase with the increase of the BBA monomer content, thereby limiting the contraction of PBA7~PBA-11. Although PBA7~PBA-11 can also respond to mercury ions, after the response, the linear polymer chain hardly contracts, loses its temperature sensitivity, and cannot reflect the characteristics of recognizing mercury ions from phase transition.

[0090] The change of the LCST value of the linear polymer's response to mercury ions minus the LCST value of its own response to deionized water is defined as ΔLCST. The ΔLCST values ​​of the two groups of polymers are as follows: Fig.10 As shown in Figures b) and d).

[0091] Example 6

[0092] In this example, the responsiveness of PNC-9 prepared in Comparative Example 3 and PBA-5 prepared in Comparative Example 2 to different metal ions was tested.

[0093] PNC-9 and PBA-5 were added to deionized water and the solutions of various metal ions (metal ions include: Li + , K + 、Na + , Rb + , Cs + 、Ag + Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ 、Zn 2+ 、Cd 2+ , Hg 2+ , Cu 2+ , Mn 2+ , Fe 2+ , Pb 2+ 、Al 3+ Cr 3+ , Fe 3+ ), the metal ion solution was prepared by dissolving the water-soluble salt of the metal ion in deionized water, the concentration of each metal ion was 1 mmol / L, and the concentration of PNC-9 and PBA-5 in deionized water and the metal ion solution was 0.1 wt%. Multiple different temperature points (20~60℃) were selected to test the transmittance of each solution at a wavelength of 500 nm.

[0094] Fig.11 The ΔLCST comparison diagram of PNC-9 prepared in Example 3 and PBA-5 prepared in Comparative Example 2 in different ion solutions. The LCST of PNC-9 in mercuric ion solution undergoes a significant shift (drops by more than 10°C), while in other various monovalent, divalent or trivalent ion solutions, the LCST of PNC-9 remains basically unchanged (changes by less than 1°C), and the selectivity coefficient is more than 10 times. The LCST of PBA-5 in various monovalent and divalent ion solutions other than mercuric ions is also basically unchanged, but in trivalent ion solutions, its LCST shifts by more than 8°C. Therefore, compared with the P(NIPAM- co- For P(NIPAM-BBA), the present invention uses C1B monomer to participate in the copolymerization to obtain P(NIPAM- co -C1B) has better mercury ion specific recognition performance and is not interfered by trivalent ions.

[0095] Example 7

[0096] In this example, the acid-base dissociation constant (p K a).

[0097] Appropriate amounts of C1B and PNC-9 were dissolved in 0.1 mol / L phosphate buffer solution, and then the acid-base dissociation constants of C1B and PNC-9 were tested by acid-base titration. Fig.12 Figure a) is the UV spectrum of C1B under different pH conditions. Fig.12 Figure b) shows the p value of C1B under different pH conditions. K aTest results, Fig.12 Figure c) is the UV spectrum of PNC-9 prepared in Example 3 under different pH conditions, Fig.12 d) is the p of PNC-9 prepared in Example 3 under different pH conditions K aTest results.

[0098] Depend on Fig.12 It can be seen that the p of C1B monomer K a is 2.79, and p of PNC-9 K a is 2.71, because in P(NIPAM -co- C1B) molecular chain, the gain and loss of protons also occurs on the C1B monomer, so the p K a is basically the same. The lower p K a means that C1B is more likely to ionize hydrogen protons, which is also the reason for the formation of [-C1B-Hg 2+ -C1B-Hg 2+ -C1B-] structure, in which the mercury ion acts as a Lewis acid (electron acceptor). Therefore, compared with the single-sided base molecule thymine (p K a>9), the double-sided base surface molecule C1B has a more suitable environment for recognizing mercury ions.

[0099] Example 8

[0100] In this example, the effect of different pH values ​​on the mercury ion response performance of PNC-9 prepared in Example 3 was tested.

[0101] PNC-9 was added into deionized water and mercury ions (Hg 2+ ) solution, and the pH value of the solution was adjusted to 2-8 with ammonia or nitric acid. The mercury ion concentration was controlled to 1 mmol / L, and the concentration of PNC-9 in deionized water and mercury ion solution under different pH conditions was 0.1 wt%. The transmittance of each solution at a wavelength of 500 nm was tested at multiple different temperature points (20-60°C). The results are as follows: Fig.13 shown.

[0102] Depend on Fig.13 It can be seen that when pH = 2-8, the thermal responsiveness of PNC-9 in deionized water and mercury ion solution does not change much, and the difference in ΔLCST at each pH value is not large, and the difference in ΔLCST is within 1°C. Therefore, when pH = 2-8, the change in pH value has little effect on P(NIPAM -co- The ion response characteristics of C1B) are basically not affected.

[0103] Example 9

[0104] In this embodiment, according to Fig.14 The route shown is to synthesize mercury ion responsive polymer smart gel-poly (N-isopropylacrylamide-co-allylbarbituric acid) hydrogel (P(NIPAM- co -C1B)hydrogel, referred to as PNC-H), has the following structural formula:

[0105]

[0106] Among them, b / (a+b)=0.09, c / a=0.033.

[0107] (1) Add monomers NIPAM and C1B, initiator ammonium persulfate (APS), and crosslinker N,N'-methylenebisacrylamide (MBA) into deionized water and stir thoroughly until the components are dissolved. Pass nitrogen through the resulting mixture for 30 min to remove oxygen from the mixture. Then add catalyst tetramethylethylenediamine (TEMED) and mix well to obtain a gel precursor solution. Immediately inject the gel precursor solution into a 40 mm × 40 mm × 1 mm mold using a syringe and crosslink at 25 °C for 24 h.

[0108] In the gel precursor solution, the molar ratio of NIPAM to initiator APS is 100:0.5, the molar ratio of NIPAM to crosslinker MBA is 100:3.3, the molar amount of C1B accounts for 9% of the sum of the molar amounts of C1B and NIPAM, and the concentration of NIPAM is 1 mol / L.

[0109] (2) After the cross-linking is completed, the obtained gel is taken out from the mold, and washed alternately in deionized water at 50°C and 5°C for 5 times. The washed gel is placed in deionized water at 25°C for equilibrium, and cut into round gels with a diameter of 11 mm for subsequent ion recognition performance tests. The hydrogel prepared in this example is recorded as PNC-H-9.

[0110] Comparative Example 3

[0111] The operation of this comparative example is basically the same as that of Example 9, except that no C1B monomer is added in step (1), and the prepared product is poly(N-isopropylacrylamide) hydrogel, denoted as PNIPAM-H.

[0112] Comparative Example 4

[0113] The operation of this comparative example is basically the same as that of Example 9, except that the monomer added in step (1) is BBA monomer, and the molar amount of BBA is controlled to be 5% of the sum of the molar amounts of BBA and NIPAM. Since the water solubility of BBA monomer is poor, the solvent deionized water in step (1) is replaced by a mixture of tetrahydrofuran and deionized water, and the volume ratio of tetrahydrofuran to deionized water in the mixture is 3:7. The final product prepared is P(NIPAM- co -BBA) hydrogel, denoted as PBA-H-5.

[0114] Example 10

[0115] In this embodiment, mercury ion responsive polymer smart gel was synthesized. The specific preparation method was basically the same as that in Example 9, except that in step (1), the molar amount of C1B monomer was controlled to account for 5%, 7%, 11% and 13% of the sum of the molar amounts of C1B monomer and NIPAM monomer, respectively. The prepared hydrogels were recorded as PNC-H-5, PNC-H-7, PNC-H-11 and PNC-H-13, respectively.

[0116] The infrared spectra of the raw material C1B and the prepared PNC-H-5, PNC-H-7, PNC-H-9, PNC-H-11, PNC-H-13 used in Examples 9 and 10, and the PNIPAM-H prepared in Comparative Example 3 are as follows: Fig.15 As shown in the figure, from the absorption peak position of PNIPAM-H, it can be seen that at 1386 cm -1 and 1367 cm -1 The characteristic absorption double peak of isopropyl belonging to NIPAM appeared at 1627 cm -1 The characteristic absorption peak of amide on NIPAM molecule appeared nearby, which appeared at 1728 cm -1 The C=O stretching vibration peak belonging to the C1B monomer also appeared on PNC-H-5, PNC-H-7, PNC-H-9, PNC-H-11 and PNC-H-13. These results show that PNC-H with different C1B contents was prepared in this example.

[0117] Embodiment 11

[0118] In this example, the temperature and mercury ion response characteristics of PNC-H with different ClB contents prepared in Examples 9 and 10 were tested.

[0119] The disc gel prepared in Examples 9 and 10 was placed in deionized water at different temperatures and a mercury ion solution with a mercury ion concentration of 0.1 mmol / L, respectively. A digital camera was used to take pictures of the disc gel at different set temperatures. The digital camera was always fixed in position and vertically aimed at the disc gel. Finally, the diameter (D T ). The test temperature range is 20~60℃. The test results are as follows Fig.16 shown.

[0120] Depend on Fig.16It can be seen that PNC-H with different C1B contents have obvious temperature response characteristics, and as the C1B content in PNC-H increases, the PNC-H disc gel can shrink to a smaller diameter. This is because barbituric acid contains special hydrogen bond donors and hydrogen bond acceptors. The increase in C1B content can increase the water content in PNC-H, so it can squeeze out more water molecules when the volume shrinks and shrink to a smaller diameter. PNC-H with different C1B contents have different degrees of mercury ion responsiveness. As the C1B content increases, the diameter of the PNC-H disc gel migrates more obviously with the temperature change curve, showing better mercury ion response performance.

[0121] Example 12

[0122] In this example, at a testing temperature of 25° C., the diameter shrinkage ratio ( R D ). In order to effectively detect the concentration of mercury ions in an unknown solution, this embodiment quantitatively proposes a range of 0 to 10 -4 mol / L concentration range, [Hg 2+ ](Hg 2+ The quantitative relationship between the concentration of the disk gel and the diameter shrinkage ratio of the disk gel is calculated by dividing the diameter of the disk gel in the mercury ion solution by its diameter in deionized water at the same test temperature.

[0123] Fig.17 The fitting relationship curve between the diameter shrinkage ratio of the PNC-H-9 disc gel prepared in Example 9 and the mercury ion concentration in different concentration mercury ion solutions is as follows: Fig.17 As shown. Fig.17 It can be seen that the relationship between the diameter shrinkage ratio of the disc gel and the mercury ion concentration can be fitted as R D =-0.0331[Hg 2+ ]+1.1228, the correlation coefficient R² of the formula is 0.9732, indicating that the formula has good fitting accuracy. When detecting the mercury ion concentration of an unknown solution, the mercury ion concentration in the solution to be tested can be estimated by measuring the diameter contraction ratio of the PNC-H-9 disc gel in the unknown solution.

[0124] By using the mercury ion responsive polymer smart gel of the present invention, the mercury ion concentration information in the solution to be tested can be obtained by simply measuring the diameter change of the disc gel without relying on other large laboratory instruments and equipment, thereby realizing portable and low-cost detection of mercury ions. By combining the mercury ion responsive polymer smart gel of the present invention with some simple and inexpensive devices, the volume contraction signal of the gel can be further accurately converted and amplified into a signal that is easier to measure, such as an electrical signal, an optical signal, a flow signal, etc., so that a sensitive, low-cost, portable mercury ion sensor can be constructed.

[0125] Example 13

[0126] In this example, the responsiveness of PNC-H-9 prepared in Example 9 and PBA-H-5 prepared in Comparative Example 4 to different metal ions was tested.

[0127] The disc gels of PNC-H-9 and PBA-H-5 were added into deionized water and various metal ion solutions (metal ions include: K + , Rb + 、Na + , Li + 、Ag + , Cu 2+ , Pb 2+ , Ba 2+ Mg 2+ 、Zn 2+ , Sr 2+ 、Co 2+ , Ca 2+ , mercury ions, Al 3+ , Fe 3 + Cr 3+ ), the metal ion solution is prepared by dissolving the water-soluble salt of the metal ion in deionized water. In the metal ion solution, the concentration of the metal ion is 0.1 mmol / L, and the temperature is controlled at 25°C. The diameter of each disc gel in deionized water and in different types of metal ion solutions is measured respectively, and the diameter shrinkage degree of each disc gel is calculated. R D The results are as follows Fig.18 shown.

[0128] Since there are two double bonds in the BBA monomer structure, both double bonds will randomly participate in the free radical polymerization reaction when preparing the hydrogel. When the double bond connected to barbituric acid in the BBA structure participates in the polymerization reaction, a hydrogel can be formed, but the hydrogel has no specific recognition of mercuric ions, such as Fig.18As shown in Figure a), PBA-H-5 has recognition reactions to most divalent metal ions and trivalent metal ions. Therefore, the hydrogel constructed with BBA as a monomer cannot be used as a device unit for constructing a signal amplification method. Fig.18 As can be seen from Figure b), the hydrogel PNC-H-9 constructed with C1B monomer of the present invention has almost no contraction response induced by other monovalent, divalent and trivalent metal ions except mercury ions, indicating that the PNC-H-9 gel has excellent specific recognition performance for mercury ions.

[0129] Relative to P(NIPAM- co -BBA) hydrogel, the mercury ion responsive polymer smart gel of the present invention has better performance of specific identification of mercury ions. In addition, since the C1B monomer is water-soluble and the synthesis method of the monomer is simpler, and the BBA monomer is hydrophobic, when constructing a hydrogel for detecting mercury ions with C1B, it has more advantages in terms of easy operation and cost reduction. Therefore, the mercury ion responsive polymer smart gel of the present invention has greater practical application advantages and transformation potential.

[0130] Embodiment 14

[0131] In this example, at a detection temperature of 25° C., the maximum mercury ion adsorption capacity of PNC-H-9 prepared in Example 9 and its adsorption effect on mercury ions in different real water samples were tested.

[0132] (1) Weigh 20 mg of freeze-dried PNC-H-9 disc gel and soak it in 50 mL of 20 mg / mL mercury ion solution for adsorption for 24 h. The maximum adsorption capacity of PNC-H-9 disc gel for mercury ions was tested by atomic absorption spectroscopy.

[0133] (2) Take 50 mL of wastewater sample and river water sample, the wastewater sample is from a sewage treatment plant, and the river water sample is from Funan River. Soak the freeze-dried PNC-H-9 disc gel in the two water samples for adsorption for 24 h, and calculate the adsorption and removal efficiency of PNC-H-9 for mercury ions by atomic absorption spectroscopy. The results are shown in Table 1.

[0134] In this embodiment, the maximum adsorption capacity of PNC-H-9 for mercury ions is 41.5 mg / g. As shown in Table 1, in different water samples, the removal efficiency of PNC-H-9 for mercury ions is between 99.1% and 99.8%, indicating that PNC-H-9 has good potential for the removal of mercury ions in actual pollution.

[0135] Table 1

[0136] Water Sample Mercury ion concentration (μg / L) Removal efficiency Funan River 0.031 99.8% Wastewater 1.8 99.1%

[0137] Embodiment 15

[0138] In this example, the repeated detection performance of PNC-H-9 prepared in Example 9 for mercury ions was tested at a detection temperature of 25°C.

[0139] The PNC-H-9 disc gel was immersed in a mercury ion solution with a concentration of 0.1 mmol / L until the diameter of the disc gel no longer changed. The diameter of the disc gel was tested and the diameter contraction ratio was calculated. The PNC-H-9 disc gel after responding to mercury ions was taken out and placed in a NaI solution, immersed for 10 min, and then transferred to deionized water, ultrasonically washed for 6 h, and the deionized water was replaced every 2 h. The cleaned PNC-H-9 disc gel was placed in a 0.1 mmol / L mercury ion solution again, and the above test was repeated. In this embodiment, the disc gel was recycled 3 times in total, and the test results are as follows: Fig.19 shown.

[0140] Depend on Fig.19 It can be seen that before and after the response, the diameter of the disc gel is not much different in the three cycles of use, and the diameter shrinkage ratio each time is also not much different, which shows that the PNC-H-9 disc gel has good stability when reused. This means that after the washing step, the gel structure is not destroyed, and the mercury ions bound to the gel can be completely eluted. This is because in the NaI solution, the mercury ions in PNC-H-9 can quickly react with NaI to form HgI precipitation, destroying the [-C1B-Hg 2 + -C1B-Hg 2+ -C1B-] structure, and then the disc gel is immersed in deionized water to gradually wash away the HgI precipitate attached to the surface of the gel to restore the gel to its original state.

[0141] Example 16

[0142] In this embodiment, the synthesis of P(NIPAM- co-C1B), the specific preparation method is basically the same as that of Example 3, except that: in step (1), the monomer NIPAM, C1B, and the initiator azobisisoheptanonitrile are added to the solvent N, N-dimethylformamide, and stirred until the components are fully dissolved to obtain a mixed solution, nitrogen is passed through the obtained mixed solution for 30 minutes under stirring to remove oxygen in the mixed solution, and then the mixture is quickly transferred to a closed container and reacted in an oil bath at 80° C. for 12 hours, the molar ratio of NIPAM to azobisisoheptanonitrile is controlled to be 100:0.5, and the concentration of NIPAM in the mixed solution is 0.1 mol / L. In step (2), the reaction solution obtained in step (1) is concentrated by a rotary evaporator until insoluble matter is just produced, and N,N-dimethylformamide is added to the concentrated reaction solution to completely dissolve the insoluble matter. The resulting solution is then added dropwise to a large amount of stirred n-hexane for precipitation, and then filtered. The resulting solid phase is vacuum dried, and the aforementioned steps of adding N,N-dimethylformamide for dissolution, precipitation with n-hexane, filtering and vacuum drying are repeated three times for the resulting crude product.

[0143] Embodiment 17

[0144] In this embodiment, P(NIPAM-co-C1B) was synthesized. The specific preparation method was basically the same as that in Example 3, except that: in step (1), monomers NIPAM, C1B, and initiator dimethyl azobisisobutyrate were added to the solvent 1, 4-dioxane, and stirred until the components were fully dissolved to obtain a mixed solution. Nitrogen was passed through the obtained mixed solution for 30 minutes under stirring to remove oxygen in the mixed solution, and then the mixture was quickly transferred to a sealed container and reacted in an oil bath at 65° C. for 36 hours. The molar ratio of NIPAM to dimethyl azobisisobutyrate was controlled to be 200:0.05.

[0145] Embodiment 18

[0146] In this embodiment, mercury ion responsive polymer smart gel was synthesized. The specific preparation method was basically the same as that in Example 9, except that the initiator used in step (1) was potassium persulfate (KPS), the molar ratio of NIPAM to KPS in the gel precursor solution was 100:0.5, the molar ratio of NIPAM to MBA was 100:1, the concentration of NIPAM was 0.5 mol / L, and crosslinking was carried out at 10°C for 24 h.

[0147] Embodiment 19

[0148] In this embodiment, mercury ion responsive polymer smart gel is synthesized. The specific preparation method is basically the same as that in Example 9, except that in the gel precursor solution, the molar ratio of NIPAM to APS is 200:0.05, the molar ratio of NIPAM to MBA is 100:7, and the concentration of NIPAM is 1.5 mol / L.

[0149] The above embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art may make some non-essential improvements and adjustments to the present invention based on the above invention content, which still fall within the scope of protection of the present invention.

Claims

1. A mercury ion responsive linear polymer, characterized in that: The structural formula of the linear polymer is shown in formula (I): (I) In formula (I), b / (a+b)=0.05~0.

11.

2. The mercury ion responsive linear polymer according to claim 1, characterized in that: In formula (I), b / (a+b)=0.07~0.

11.

3. The method for preparing the mercury ion responsive linear polymer according to claim 1, characterized in that: The following steps are involved: (1) dissolving N-isopropylacrylamide monomer, allyl barbituric acid monomer and initiator in a solvent to obtain a mixed solution, passing nitrogen gas into the mixed solution to remove oxygen in the mixed solution, and then reacting in a sealed container at 65-80° C. for 12-36 hours; In this step, the molar ratio of the N-isopropylacrylamide monomer to the initiator in the mixed solution is controlled to be (100-200): (0.05-0.5), and the molar amount of the allylbarbituric acid monomer accounts for 5%-11% of the sum of the molar amounts of the allylbarbituric acid monomer and the N-isopropylacrylamide monomer; (2) Separating and purifying the mercury ion-responsive linear polymer from the reaction solution obtained in step (1) by a precipitation method.

4. The method for preparing the mercury ion responsive linear polymer according to claim 3, characterized in that: In the mixed solution of step (1), the concentration of N-isopropylacrylamide monomer is 0.1-0.4 mol / L.

5. The method for preparing the mercury ion responsive linear polymer according to claim 3 or 4, characterized in that: The initiator in step (1) is azobisisobutyronitrile, azobisisoheptanenitrile or dimethyl azobisisobutyrate.

6. The method for preparing the mercury ion responsive linear polymer according to claim 3 or 4, characterized in that: The solvent in step (1) is tetrahydrofuran, N, N-dimethylformamide or 1, 4-dioxane.

7. A mercury ion responsive polymer smart gel, characterized in that: The structural formula of the polymer of the polymer smart gel is shown in formula (II): (II) In formula (II), b / (a+b)= 0.05~0.13, c / a=0.01~0.

07.

8. The method for preparing the mercury ion responsive polymer smart gel according to claim 7, characterized in that: The following steps are involved: Dissolving N-isopropylacrylamide monomer, allylbarbituric acid monomer, initiator and cross-linking agent N,N'-methylenebisacrylamide in water to obtain a mixed solution, passing nitrogen gas into the mixed solution to remove oxygen in the mixed solution, then adding a catalyst to obtain a gel precursor solution, reacting the gel precursor solution at 10-25° C. until it is converted into a gel state, and washing to remove unreacted raw materials to obtain; In the gel precursor solution, the molar ratio of N-isopropylacrylamide monomer to initiator is (100~200):(0.05~0.5), the molar ratio of N-isopropylacrylamide monomer to cross-linking agent is 100:(1~7), the molar amount of allylbarbituric acid monomer accounts for 5%~13% of the sum of the molar amounts of allylbarbituric acid monomer and N-isopropylacrylamide monomer, and the concentration of N-isopropylacrylamide monomer is 0.5~1.5 mol / L.

9. The method for preparing the mercury ion responsive polymer smart gel according to claim 8, characterized in that: The catalyst is tetramethylethylenediamine.

10. The method for preparing the mercury ion responsive polymer smart gel according to claim 8 or 9, characterized in that: The initiator is ammonium persulfate or potassium persulfate.

Citation Information

Patent Citations

  • Thermo-sensitive linear polymer material with double base planes for identifying Hg < 2 + > and preparation method of thermo-sensitive linear polymer material

    CN116239720A

  • Mercury ion detection probe, and preparation method and application thereof

    CN109705111A

  • Polymer based on diallyl malonyl urea and preparation method thereof

    CN110483669A